Social intervention recommendations for depressed women with insecure styles, correlated with risk factors. - Nor Ba’yah Abdul Kadir, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
A list of social interventions for insecure and depressed Malay women was recommended in order to enhance their well-being and social functioning. In order to develop an intervention program for insecure and depressed women and to see if these attachment styles related to support, self-esteem, and life events, would also be correlated with depression symptomatology, a preliminary study is crucial. A thousand and two mothers completed questionnaires assessing severe life events (RLEQ), psychosocial vulnerability (VASQ), and the General Health Questionnaire-30 to assess depression. The Attachment Style Interview (ASI) was used to tap attachment styles and Structured Clinical Interview for DSM-IV (SCID) to assess depression. The 61 women interviewed were selected on the basis of high General Health Questionnaire scores from a large questionnaire survey of 1,002 mothers. Findings have shown that 60.5% of single mothers and 39.5% of married mothers have depressive symptoms. Fearful styles were the most common (43.3%) and high proportion of the women exhibited Dual/Disorganised style (29.5%). The study suggested several social interventions: increasing psychotherapy and counselling services, raising public awareness, providing professional training for clinical psychologists and increasing treatment availability.